Recursos tecno-metodológicos para descrição e recuperação de informações na Web - Santarem Segundo, José Eduardo [UNESP] (Universidade Estadual Paulista (Unesp), 2004)
The technology brought to Information Science a new particle in its object of study - the information in the Web; it brought, also, a very great approach enters sciences of the Information and the Computation. The Internet comes growing of frightful form, developing the explosion of Information, of form the terms a countless amount of available information in the Web. In this way, one becomes necessary to investigate technologies for description and recovery of information that make possible the organization of the digital information in the scope of the World Wide Web. Using itself documentary research in sources of the areas of Computer Science and Information Science and proper net Internet had been analyzed the main languages and the resources for publication of information in the Web, the forms of description and recovery of information, the proposals of new standards and structure of boarded data and the new tools that they come being argued and implemented, objectifying the organization of the digital information.The delineation of a Semantic Web was verified, that if deals with an extension of the current Web and that it considers a new architecture, thus let us can give meant to all information found in this new concept of Internet. Such aspects allow to conclude that the creation of the Semantic Web is a time question and that, in briefing, this new extension of the Web will inside start to be a consistent and qualified piece of information of the Internet, making possible to some communities the construction of knowledge from found trustworthy data in the net.

A tecnologia trouxe à Ciência da Informação uma nova partícula em seu objeto de estudo - a informação na Web; trouxe, também, uma aproximação muito grande entre as Cências da Informação e da Computação. A Internet vem crescendo rapidamente, incrementando a explosão de informações, de forma a termos uma grande quantidade de informação disponível na Web. Desse modo, torna-se necessário investigar tecnologias para descrição e recuperação de informações que possibilitem a organização da informação digital no âmbito da World Wide Web. Valendo-se de pesquisa documental em fontes das áreas de Ciência da Computação e Ciência da Informação e da própria rede Internet foram analisadas as principais linguagens e os recursos para publicação de informações na Web, as formas de descrição e recuperação de informação, as propostas de novos padrões e de estrutura de dados e abordadas as novas ferramentas que vêm sendo discutidas e implementadas, objetivando a organização da informação digital. Verificou-se o delineamento de uma Web Semântica, que se trata de uma extensão da Web atual e que propõe uma nova arquitetura, de maneira que possamos dar significado a toda informação encontrada neste novo conceito de Internet. Tais aspectos permitem concluir que a criação da Web Semântica é uma questão de tempo e que, em breve, essa nova extensão da Web passará a ser um pedaço consistente e qualificado de informações dentro da Internet, possibilitando a várias comunidades a construção de conhecimento a partir de dados confiáveis encontrados na rede.
Keywords: Internet; Redes de computadores; XML (Linguagem de marcação de documento); Sites da Web - Desenvolvimento; Recuperação da informação; Semantic Web; Markup Languages; Tools of Search; Description and recovery of information in the Web